Curriculum review: serrated lesions of the colorectum. Issue 3 (5th June 2019) - Dhillon, Angad Singh; Ibraheim, Hajir; Green, Susi; Suzuki, Noriko; Thomas-Gibson, Siwan; Wilson, Ana
Abstract : Colorectal cancer (CRC) is the second leading cause of death from cancer in the UK. Sporadic CRC evolves by the cumulative effect of genetic and epigenetic alterations. Typically, over the course of several years, this leads to the transformation of normal colonic epithelium to benign adenomatous polyp, low-grade to high-grade dysplasia and finally cancer—the adenoma-carcinoma sequence. Over the last decade, the serrated neoplasia pathway which progresses by methylation of tumour suppressing genes has been increasingly recognised as an important alternative pathway accounting for up to 30% of CRC cases. Endoscopists should be aware of the unique features of serrated lesions so that their early detection, appropriate resection and surveillance interval can be optimised.